Novel photovoltaic glass antireflection coating process based on float glass

The anti-reflective film layer with a specific micro-nano periodic structure was prepared on photovoltaic glass by template transfer method, which solved the problems of high production costs and low transmittance of traditional photovoltaic glass, and achieved efficient photovoltaic glass production.

CN119285250APending Publication Date: 2025-01-10CHINA LUOYANG FLOAT GLASS GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411523712.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional photovoltaic glass has high production costs and is difficult to meet the needs of large size and uniform thickness. At the same time, traditional anti-reflective films are difficult to improve the transmittance of glass, limiting the production efficiency of photovoltaic glass.

Method used

An anti-reflection coating with a specific micro-nano periodic structure was prepared on flat glass by template transfer method. Through the cooperation of the target structure template and the transition template, an efficient anti-reflection film layer is formed on the glass surface and the transmittance is improved.

Benefits of technology

It realizes the rapid and efficient formation of anti-reflective film layer with high transmittance on flat glass, which meets the processing needs of photovoltaic glass produced by ultra-white float glass process, reduces production costs and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285250A_ABST
    Figure CN119285250A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photovoltaic glass coating, and particularly relates to a novel photovoltaic glass antireflection coating process based on float glass, specifically, an operator can design a target structure template and a transition template in advance; coating the surface of the target structure template with a thermoplastic or thermosetting template material, and maintaining the pressure at a certain temperature; the temperature is kept higher than the glass transition temperature of the soft material in the imprinting process, so that the polymer is in a softened state; the method comprises the following steps: uniformly spraying an antireflection film coating liquid on the surface of the plate glass, carrying out film structure printing by adopting a transition template with a target structure and a reflection structure, and the like, so that an antireflection film layer with a target structure is quickly and efficiently formed on the surface of the plate glass, and the processing requirement of producing photovoltaic glass through an ultra-white float glass process is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaic glass coating, and in particular relates to a novel photovoltaic glass anti-reflection coating process based on float glass. Background Art

[0002] At present, the mainstream product of photovoltaic glass is rolled glass. The ultra-white rolled glass process has become the mainstream production process of photovoltaic glass due to its high light transmittance. Compared with ultra-white float glass, the front of ultra-white rolled glass adopts a special velvet treatment, which effectively reduces the reflection of light, and the back adopts a special pattern treatment, which greatly enhances the transmittance of sunlight at different incident angles. The superimposed product body has a high transmittance, ensuring that the ultra-white rolled glass can maintain excellent transmittance under long-term sunlight exposure. However, due to the large investment in the production line of ultra-white rolled glass, the difficulty in manufacturing, and the high precision requirements for raw materials, the preparation cost of ultra-white rolled glass is high, which is suitable for the production of glass with fixed size and thickness. Ultra-white float glass is easy to form, has high production efficiency, has the advantages of low cost and high processing yield, and is suitable for the production of large-size, uniform thickness and easy-to-adjust glass. If a higher transmittance can be obtained, the efficiency of photovoltaic glass production will be greatly improved. At the same time, it is increasingly difficult for traditional anti-reflection films to increase the transmittance of glass. Therefore, it is imperative to develop a new photovoltaic glass anti-reflection film based on float technology and its production process. Summary of the invention

[0003] The purpose of the present invention is to provide a novel photovoltaic glass anti-reflection coating process based on float glass. The novel photovoltaic glass anti-reflection coating process adopts a template transfer method to print a film structure on a flat glass original sheet. The overall operation process is simple and convenient, and the flat glass can obtain a higher transmittance, thereby meeting the processing needs of producing photovoltaic glass through the ultra-clear float glass process.

[0004] In order to achieve the above object, the present invention adopts the following technical solution: A novel photovoltaic glass anti-reflection coating process based on float glass comprises the following steps: S1. Preparation of a structural template: The structural template is divided into two parts, a target structural template (2) and a transition template (3); the target structural template is a template having a target structure on its surface, wherein the target structure is a micro-nano periodic structure having protrusions of a specific shape. To ensure the stability of the structure, the target structural template is made of a rigid material and is obtained by etching and sputtering. S2. Preparation of transition template: The surface structure of the transition template is opposite to that of the target structure template, and both are micro-nano periodic structures with protrusions of specific shapes; a thermoplastic or thermosetting soft material is coated on the surface of the target structure template, and a suitable holding temperature is selected according to the selected transition template material. The temperature should be higher than the glass transition temperature of the selected soft material, so that the polymer is always in a softened state during the imprinting process. After the imprinting is completed and the template is cured and demolded, a transition template with the reverse structure of the target structure template can be obtained; S3, spraying a layer of anti-reflection coating liquid uniformly on the surface of the flat glass, using the transition template with the reverse structure of the target structure template in step S2 to print the film structure, and forming an anti-reflection film layer with the target structure on the surface of the flat glass after drying and sintering.

[0005] Furthermore, the specific shape of the target structure is a micro-nano periodic structure of columnar or Gaussian surface protrusions. To ensure the stability of the target structure template, the target structure template uses a rigid material SiC plate or silicon plate, and adopts an inductively coupled plasma (ICP) etching method to obtain a surface with a protrusion top width of 40-50nm and a protrusion period of 180-230nm.

[0006] Furthermore, in step S2, methyl methacrylate (PMMA) is coated on the surface of the target structure template, and the template is kept at 120° C. and 80 atmospheres for 10 minutes. After curing and demolding, a transition template having the reverse structure of the target structure template can be obtained.

[0007] Furthermore, in step S2, in order to facilitate demoulding and ensure film integrity, the transition template is made of soft material.

[0008] Furthermore, in step S3, the film surface of the anti-reflection film layer is a surface formed by the accumulation of nanoparticles in the anti-reflection film plating solution and has a periodic convex structure, the convex top width of the convex structure is 40-50nm, and the convex period is 180-230nm.

[0009] The beneficial effects of the present invention are as follows: a novel photovoltaic glass anti-reflection coating process based on float glass provided by the present invention can coat a layer of anti-reflection film with a certain structure on the surface of flat glass during operation, so as to achieve a higher transmittance of the flat glass, thereby meeting the processing needs of producing photovoltaic glass through the ultra-white float glass process; specifically, an operator can pre-design a target structure template and a transition template; coat a thermoplastic or thermosetting template material on the surface of the target structure template and maintain pressure at a certain temperature; maintain a temperature higher than the glass transition temperature of the soft material during the printing process to keep the polymer in a softened state; uniformly spray an anti-reflection coating liquid on the surface of the flat glass, use a transition template with a reverse structure of the target structure to print the film structure, and other steps, thereby quickly and efficiently forming an anti-reflection film layer with a target structure on the surface of the flat glass, thereby meeting the processing needs of producing photovoltaic glass through the ultra-white float glass process. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a structural relationship diagram between a target structure template and a transition template in the anti-reflection coating process of the present invention; Figure 2 It is a relationship diagram of the transition template, the anti-reflection film structure and the flat glass in the anti-reflection coating process of the present invention; Figure 3 This is a SEM image of the surface structure of the membrane obtained in Example 1 of the present invention; Figure 4 This is a SEM image of the membrane surface observed at 45° obtained in Example 1 of the present invention; The numbers in the figure are: 1-flat glass, 2-target structure template, 3-transition template, 4-anti-reflection film. DETAILED DESCRIPTION

[0011] Specific embodiment 1: The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. It should be noted that: in the present invention, if there is no special description, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical scheme. In the present invention, if there is no special description, all the technical features and preferred features mentioned herein can be combined with each other to form a new technical scheme. The "scope" disclosed in the present invention is in the form of lower limit and upper limit, which can be one or more lower limits, and one or more upper limits respectively. In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in sequence.

[0012] As the instruction manual Figure 1, Instruction Manual Figure 2 As shown, the novel photovoltaic glass anti-reflection coating process of the present invention adopts a template transfer method to print the film structure on the original flat glass 1. The overall operation process is simple and convenient, and the flat glass 1 can obtain a higher transmittance, meeting the processing needs of producing photovoltaic glass through the ultra-clear float glass process; specifically, the novel photovoltaic glass anti-reflection coating process of the present invention mainly includes the following steps: S1. Preparation of structural template: The structural template is divided into two parts, target structural template 2 and transition template 3. To ensure the stability of the structure, the target structural template 2 is made of rigid material (SiC plate or silicon plate, etc.) and is made by etching and sputtering methods. S2. Preparation of transition template: Coat the surface of the target structure template with thermoplastic or thermosetting soft material, select a suitable holding temperature according to the selected transition template material, the temperature should be higher than the glass transition temperature of the selected soft material, so that the polymer is always in a softened state during the imprinting process, and after the imprinting is completed and the template is cured and demolded, a transition template with the inverse structure of the target structure template can be obtained; S3, spraying a layer of anti-reflection coating liquid uniformly on the surface of the flat glass 1, using the transition template 3 with the reverse structure of the target structure template 2 in step S2 to print the film structure, and forming an anti-reflection film 4 with the target structure on the surface of the flat glass 1 after drying and sintering.

[0013] In order to enable those skilled in the art to have a clearer understanding of the present invention, the following is an example of a photovoltaic glass factory using a template transfer process to print a film structure on a flat glass 1 original sheet to prepare a photovoltaic glass anti-reflection film 4: The production line uses an anti-reflection coating liquid product whose main component is modified SiO2 to coat a bionic nano anti-reflection film 4 with a papillary structure on the surface of a flat glass 1. The target structural parameters of the anti-reflection film 4 are: convex top width 40-50nm, convex period 180-230nm; firstly, a structural template is prepared; as shown in the attached manual Figure 1 As shown, the structure template can be divided into two parts: target structure template 2 and transition template 3. In order to ensure the stability of the structure of target structure template 2, the target structure template 2 material uses silicon plate, and the target structure template 2 is prepared by inductively coupled plasma (ICP) etching method. The ICP method uses CF4 / 02 as etching gas, the ICP source power is 300 watts, the CF4 / 02 flow rate is 20:10sccm, and the working pressure is 2.5Pa. The surface with a protrusion top width of 40-50nm and a protrusion period of 180-230nm is obtained, and then polymethyl methacrylate PMMA is coated on the surface of the target structure template 2, and the pressure is maintained at 120°C and 80 atmospheres for 10 minutes. After curing and demolding, the transition template 3 with the inverse structure of the target structure template 2 can be obtained; In the specific actual production, the coating production process is adopted, that is, a layer of anti-reflection coating liquid is uniformly sprayed on the surface of the flat glass 1, and the film structure is printed using the prepared transition template 3 with the reverse structure of the target structure template 2, and a layer of anti-reflection film 4 is formed on the surface of the flat glass 1 after drying and sintering; the coating sample is collected for surface morphology observation, and the surface morphology of the coating sample is observed from the attached manual. Figure 3 It can be seen from the SEM image of the surface structure of the prepared film that the surface of the film is a surface formed by the accumulation of nanoparticles in the coating solution and has a structure with many periodic protrusions, the top width of the protrusions is 40-50nm, and the protrusion period is 180-230nm.

[0014] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A novel photovoltaic glass anti-reflection coating process based on float glass, characterized in that: The steps include: S1. Preparation of a structural template: The structural template is divided into two parts, a target structural template (2) and a transition template (3); the target structural template is a template having a target structure on its surface, wherein the target structure is a micro-nano periodic structure having protrusions of a specific shape. To ensure the stability of the structure, the target structural template (2) is made of a rigid material, and the target structural template having the target structure on its surface is prepared by etching and sputtering. S2. Preparation of transition template: The surface structure of the transition template is opposite to that of the target structure template, and both are micro-nano periodic structures with protrusions of specific shapes; a thermoplastic or thermosetting soft material is coated on the surface of the target structure template, and a suitable holding temperature is selected according to the selected transition template material. The temperature should be higher than the glass transition temperature of the selected soft material, so that the polymer is always in a softened state during the imprinting process. After the imprinting is completed and the template is cured and demolded, a transition template with the reverse structure of the target structure template can be obtained; S3, spraying a layer of anti-reflection coating liquid uniformly on the surface of the flat glass, using the transition template with the reverse structure of the target structure template in step S2 to print the film structure, and forming an anti-reflection film layer with the target structure on the surface of the flat glass after drying and sintering.

2. According to claim 1, a novel photovoltaic glass anti-reflection coating process based on float glass is characterized in that: The specific shape of the target structure is a micro-nano periodic structure of columnar or Gaussian surface protrusions. In order to ensure the stability of the target structure template, the target structure template (2) uses a rigid material SiC plate or silicon plate, and adopts an inductively coupled plasma (ICP) etching method to prepare the target structure template (2). The ICP method uses CF4 / 02 as an etching gas, the ICP source power is 300 watts, the CF4 / 02 flow rate is 20:10 sccm, and the working pressure is 2.5 Pa. The surface with a protrusion top width of 40-50nm and a protrusion period of 180-230nm is obtained.

3. The novel photovoltaic glass anti-reflection coating process based on float glass according to claim 2, characterized in that: In step S2, methyl methacrylate (PMMA) is coated on the surface of the target structure template (2), and the mixture is kept at 120° C. and 80 atmospheres for 10 minutes. After curing and demoulding, a transition template (3) having the inverse structure of the target structure template (2) is obtained.

4. The novel photovoltaic glass anti-reflection coating process based on float glass according to claim 3, characterized in that: In step S2, in order to facilitate demoulding and ensure film integrity, the transition template (3) is made of soft material.

5. The novel photovoltaic glass anti-reflection coating process based on float glass according to claim 3, characterized in that: In step S3, the film surface of the anti-reflection film (4) layer is a surface formed by the accumulation of nanoparticles in the anti-reflection film plating solution and has a periodic convex structure, the convex top width of the convex structure is 40-50nm, and the convex period is 180-230nm.